Analisis Tingkat Kesehatan Perusahaan dari Aspek Keuangan Berdasarkan Keputusan Menteri BUMN Nomor: KEP-100/MBU/2002 : (Studi Kasus Pada PT. Krakatau Steel (Persero) Tbk Periode 2017-2021) - Meri Dita Rahayu; Indah Listyani; Edi Murdiyanto (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to determine the level of company health from a financial aspect based on the Decree of the Minister of BUMN Number: KEP-100/MBU/2002 at PT. Krakatau Steel (Persero) Tbk for the 2017-2021 period. The method used in this research is quantitative descriptive. This health level assessment uses 8 financial aspect indicators, namely ROE, ROI, Cash Ratio, Current Ratio, Collection Periods, Inventory Turnover, Total Asset Turn Over, and Total Own Capital to Total Assets. Based on the research results, PT. Krakatau Steel (Persero) Tbk for the 2017-2021 period experienced increases and decreases as seen from 8 financial ratio indicators. The financial health assessment in 2017 and 2018 was in the unhealthy predicate in the BBB category with a final score of 55 in 2017 and 53.21 in 2018, however in 2019 it was in the unhealthy predicate in the CCC category with a final score of 30, whereas in 2020 it was ranked as unhealthy in the BB category with a final score of 47.14 and in 2021 it was ranked as unhealthy in the BBB category with a final score of 55. So it can be concluded that the financial health of PT. Krakatau Steel (Persero) Tbk is in an unhealthy condition.